Contribution to the taxonomy of the Southeast Asian Mesochorinae (Hymenoptera, Ichneumonidae) - Riedel, Matthias (Zootaxa, 2023)
In this taxonomical study, one new genus and 41 new species of the subfamily Mesochorinae (Hymenoptera, Ichneumonidae) are described from Southeast Asia, namely from Indonesia, Malaysia, Thailand and Vietnam. The new genus is Orientochorus n. gen., the new species are Orientochorus tonkinensis n. sp., Astiphromma bicoloratus n. sp., Mesochorus achterbergi n. sp., Mesochorus anamnesis n. sp., Mesochorus brevipunctatus n. sp., Mesochorus cariniscuta n. sp., Mesochorus controversus n. sp., Mesochorus diversidens n. sp., Mesochorus flavator n. sp., Mesochorus flavopronotalis n. sp., Mesochorus fuscomaculatus n. sp., Mesochorus halmaherae n. sp., Mesochorus harlequinus n. sp., Mesochorus kinabaluensis n. sp., Mesochorus lamdongensis n. sp., Mesochorus longimurus n. sp., Mesochorus longistylus n. sp., Mesochorus longivalvator n. sp., Mesochorus malaysiacus n. sp., Mesochorus malucutus n. sp., Mesochorus nigripleuris n. sp., Mesochorus nigrofemur n. sp., Mesochorus nigromaculatus n. sp., Mesochorus paratenebris n. sp., Mesochorus pictiloides n. sp., Mesochorus pterostigmator n. sp., Mesochoprus rufator n. sp., Mesochorus sabahensis n. sp., Mesochorus sapaensis n. sp., Mesochorus semifuscus n. sp., Mesochorus semipunctatus n. sp., Mesochorus siamensis n. sp., Mesochorus stigmaticolor n. sp., Mesochorus striatofacies n. sp., Mesochorus sulaensis n. sp., Mesochorus sumaterae n. sp., Mesochorus templator n. sp., Mesochorus tenebris n. sp., Mesochorus tonkinensis n. sp., Mesochorus train n. sp., and Mesochorus vietnamensis n. sp. All species are illustrated and described in detail. In addition, a key for the females of the known Mesochorus species of Southeast Asia is presented.